Characterization of the potential allergenicity of irradiated bovine α-lactalbumin in a BALB/c mouse model. (November 2016) - Meng, Xuanyi; Li, Xin; Gao, Jinyan; Chen, Hongbing
Abstract: Bovine α-lactalbumin (ALA) is a known food allergen present in milk to induce anaphylaxis. A previous study demonstrated that irradiated ALA (iALA) decreased the IgE-binding properties and weakened the degranulation capacity of basophils in vitro . The present study aimed to further assess the potential allergenicity of iALA in vivo in a BALB/c mouse model. The mice (n = 10/group) were intragastrically sensitized and orally challenged with either iALA or ALA using cholera toxin as adjuvant. In contrast to the ALA group, the iALA group did not show anaphylactic shock symptoms. A tendency toward decreased serum allergen-specific IgG/IgG1 /IgE levels, plasma histamine levels and mast cell protease-1 (mMCP-1) concentrations in the iALA group were also observed, accompanied by a decrease in Th2-related cytokine levels and an increase of IFN-γ production in spleen cell cultures. Moreover, the peritoneal mast cell surface expression of FcεRI and peripheral blood basophil CD200R + expression were decreased by 64.3% and 35.19%, respectively. Conversely, the percentage of CD4 + CD25 + Foxp3 + regulatory T cells increased in the iALA group. All of these findings indicated that iALA induces a shift toward the Th1 response, which ultimately reduces its potential allergenicity. Graphical abstract: Highlights: Potential allergenicity of irradiated α-La (iALA) was investigated using a BALB/c mouse model. iALA did not induce remarkable allergenic reactions in BALB/c mice. iALA induces a shift toward the Th1 response, which ultimately reduces its potential allergenicity. iALA is not allergenic under irradiation processing using safe doses.